A physiologically based pharmacokinetic model of voriconazole integrating time-dependent inhibition of CYP3A4, genetic polymorphisms of CYP2C19 and predictions of drug-drug interactions - Li, Xia; Frechen, Sebastian; Moj, Daniel; Lehr, Thorsten; Taubert, Max; Hsin, Chih-hsuan; Mikus, Gerd; Neuvonen, Pertti J.; Olkkola, Klaus T.; Saari, Teijo I.; Fuhr, Uwe (Clinical pharmacokinetics, 2020)
Voriconazole, a first-line antifungal drug, exhibits nonlinear pharmacokinetics (PK), together with large interindividual variability but a narrow therapeutic range, and markedly inhibits cytochrome P450 (CYP) 3A4 in vivo. This causes difficulties in selecting appropriate dosing regimens of voriconazole and coadministered CYP3A4 substrates.
Gesehen am 23.07.2020
First published: 19 December 2019